Assessing the perception and reality of arguments against thermal waste treatment plants in terms of property prices - Philips, K. J. O.; Longhurst, Philip J.; Wagland, Stuart T. (Elsevier, 2013)
The thermal processing of waste materials, although considered to be an essential part of waste management, is often sharply contested in the UK. Arguments such as health, depletion of resources, cost, noise, odours, traffic movement and house prices are often cited as reasons against the development of such facilities. This study aims to review the arguments and identify any effect on property prices due to the public perception of the plant. A selection of existing energy from waste (EfW) facilities in the UK, operational for at least 7 years, was selected and property sales data, within 5 km of the sites, was acquired and analysed in detail. The locations of the properties were calculated in relation to the plant using GIS software (ArcGIS) and the distances split into 5 zones ranging from 0 to 5 km from the site. The local property sale prices, normalised against the local house price index, were compared in two time periods, before and after the facility became operational, across each of the 5 zones. In all cases analysed no significant negative effect was observed on property prices at any distance within 5 km from a modern operational incinerator. This indicated that the perceived negative effect of the thermal processing of waste on local property values is negligible.
Keywords: Energy from waste; Thermal waste treatment; Public perception; Property prices